Populasi dan Habitat Ungko (Hylobates agilis) di Taman Nasional Batang Gadis, Sumatera Utara - Tuah Malem Bangun; Sri Supraptini Mansjoer; M. Bismark (Jurnal Primatologi Indonesia, 2009)
Ungko/mountain agile gibbon (Hylobates agilis) is one of Sumatera endemic gibbon and is considered a near threatened spesies. The aim of this research was to study the population and habitat of mountain agile gibbon (ungko) at Batang Gadis National Park. Surveyed on population of ungko and habitat condition were conducted three-months period (July-September 2005). Methods used were line transect for population estimation and ungko habitat was analysed by block line method. The average group size density for ungko at the study area was 2.60 groups/km2, group size was estimated at 3.41 animals, and the population density was estimated 8.82 individuals/km2. There were 2,240 groups, and 7,620 individuals in Batang Gadis National Park. The vegetations were dominated by Geunsia farinosa, Mallotus sp. and Litsea elliptica. Food sources for the ungko were dominated by Geunsia farinosa, Craton laevifolius, Myristica iners and  Syzygium sp.    Keywords: ungko (Hylobates agilis), population, habitat